NUTRITIONAL INTAKE AND ITS IMPACT ON PHYSICAL ENDURACE AND STAMINA OF TAEKWONDO ATHLETES - Mufarrohah, Siti; Supriyadi, Tedi; Dinangsit, Dinar (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2025)
Physical endurance is the body's ability to sustain physical activity for an extended period without experiencing excessive fatigue. Proper nutrition, physical endurance, and stamina are factors that influence performance, especially in taekwondo athletes. This study aimed to examine the relationship between proper nutrition and physical endurance and stamina. Using a correlational design and a quantitative approach, this study involved 30 athletes selected using a total sampling technique. Data was analyzed using SPSS 22 software. Dietary intake data was collected through a 24-hour food recall questionnaire for 4 consecutive days, while physical endurance was measured using the 12-minute run test (Cooper Test). The results of the analysis showed a significant positive correlation between nutritional intake and physical endurance/stamina, with a Pearson correlation coefficient r = 0.68 and p-value = 0.002, indicating that the better the nutritional intake, the better the physical endurance and stamina of the athletes. Dietary intake data revealed that 78.6% of athletes did not meet the recommended daily nutritional requirements, with 76.67% of athletes having a caloric intake of less than 110% of their daily energy requirements. This indicates that athletes with good nutritional intake have better performance during training and competition.